Compact Dual Band Antenna Design for Ku / Ka Band Applications - A. Kandwal (Advanced Electromagnetics, 2017)
This communication proposes a compact 16 GHz / 30 GHz dual band antenna design for Ku / Ka band applications. The antenna consists of two layers with lower layer having the fed patch and the upper layer having non-periodic element array. The antenna has been designed to operate at two different frequencies with compact dimensions of (8mm x 8mm) using Rogers RT 5880. The compact size of this proposed antenna also makes it suitable for integration with the microwave and millimeter wave circuits. The proposed antenna provides high radiation efficiency and a peak gain of about 8 dB at the resonant frequencies with reduced side lobe levels.